Maternal functional hemodynamics in uncomplicated twin pregnancies: A longitudinal study using impedance cardiography. (6th November 2018) - Orabona, Rossana; Prefumo, Federico; Zanardini, Cristina; Magri, Roberta; Loardi, Chiara; Cappa, Veronica; Calza, Stefano; Frusca, Tiziana; Acharya, Ganesh
Abstract: Introduction: Longitudinal studies of maternal hemodynamics in twin pregnancy are scarce and preload reserve in twin pregnancies has not been studied. Thus, we aimed to investigate serial changes in maternal systemic hemodynamics from the first to third trimester, and cardiovascular response to passive leg raising to evaluate preload reserve using impedance cardiography in a cohort of uncomplicated twin pregnancies. Material and methods: This was a prospective longitudinal study of 50 twin pregnancies. Maternal hemodynamics was assessed at baseline and 120 seconds after passive leg raising using impedance cardiography, at five time points during gestation. Women were excluded from the analysis if there were pregnancy complications or fewer than three of five planned assessments were available. Results: Data from 37 uncomplicated twin pregnancies were available for analysis. Mean arterial pressure slightly decreased until 17 weeks' gestation, then increased. Systemic vascular resistance was constant in the first half of pregnancy before rising steadily thereafter, whereas the cardiac output increased from the first trimester, peaked by the end of the second trimester and then decreased in the third trimester. The change in stroke volume and cardiac output following passive leg raising during pregnancy ranged from −2.2% to 1.6% and from −3.7% to 3.2%, respectively. Although passive leg raising caused no significant changes in systemic vascular resistance, cardiac output or heart rate, mean arterial pressure decreased in the first and second trimesters. Conclusions: In uncomplicated twin pregnancies, maternal cardiovascular adaptation is evident from the first trimester. Twin pregnancies show a reduced preload reserve in the second half of gestation.